Human-pathogenic relapsing fever Borrelia found in bats from Central China phylogenetically clustered together with relapsing fever borreliae reported in the New World. - Ze-Min Li; Xiao Xiao; Chuan-Min Zhou; Jian-Xiao Liu; Xiao-Lan Gu; Li-Zhu Fang; Bin-Yan Liu; Lian-Rong Wang; Xue-Jie Yu; Hui-Ju Han (Public Library of Science (PLoS), 2021)
Bats can harbor zoonotic pathogens causing emerging infectious diseases, but their status as hosts for bacteria is limited. We aimed to investigate the distribution, prevalence and genetic diversity of Borrelia in bats and bat ticks in Hubei Province, China, which will give us a better understanding of the risk of Borrelia infection posed by bats and their ticks. During 2018-2020, 403 bats were captured from caves in Hubei Province, China, 2 bats were PCR-positive for Borrelia. Sequence analysis of rrs, flaB and glpQ genes of positive samples showed 99.55%-100% similarity to Candidatus Borrelia fainii, a novel human-pathogenic relapsing fever Borrelia species recently reported in Zambia, Africa and Eastern China, which was clustered together with relapsing fever Borrelia species traditionally reported only in the New World. Multilocus sequence typing (MLST) and pairwise genetic distances further confirmed the Borrelia species in the bats from Central China as Candidatus Borrelia fainii. No Borrelia DNA was detected in ticks collected from bats. The detection of this human-pathogenic relapsing fever Borrelia in bats suggests a wide distribution of this novel relapsing fever Borrelia species in China, which may pose a threat to public health in China.